Pengaruh Waktu Fermentasi Teh Kombucha terhadap Penurunan Kadar Glukosa Darah pada Tikus Putih Jantan Galur Wistar dengan Induksi Aloksan - Nilam Kristianingtyas; Inaratul Rizkhy Hanifah; Iswandi Iswandi (Jurnal Farmasi Indonesia, 2015)
Diabetes mellitus is a group of metabolism disorders which is characteristic by the blood glucosa levels. Kombucha tea is a fermented product of sweet tea due o activity of yeast and bacteria.The research was aimed to determine the influence of various kombucha fermentation time on the decrease of glucose level in white male rats wistar. The tested animal is were inducted with aloksan and arranged into groups. Each group consisted of 5 white male rats. Group I as negative control was treated by aquadest. Group II, III dan IV were treated by 5,5 ml of 4, 8 and 12 days-fermentation kombucha tea, respectively. Group V, as positive control was treated by glibenclamide at 0,09 mg/200 g BB. The treatments were conducted for two weeks. Each group was observed for glucose levels an the firstand second week. The results were analyzed using one way ANOVA. The result showed that tea kombucha is able to decreaseglucose levels and the 12 days fermented kombucha tea has ability to decrease glucose levels better than 4 and 8 days fermented tea kombucha.